The effect of prescribed burning on plant rarity in a temperate forest. Issue 3 (8th January 2018) - Patykowski, John; Holland, Greg J.; Dell, Matt; Wevill, Tricia; Callister, Kate; Bennett, Andrew F.; Gibson, Maria
Abstract: Rare species can play important functional roles, but human‐induced changes to disturbance regimes, such as fire, can inadvertently affect these species. We examined the influence of prescribed burns on the recruitment and diversity of plant species within a temperate forest in southeastern Australia, with a focus on species that were rare prior to burning. Floristic composition was compared among plots in landscapes before and after treatment with prescribed burns differing in the extent of area burnt and season of burn (before–after, control‐impact design). Floristic surveys were conducted before burns, at the end of a decade of drought, and 3 years postburn. We quantified the effect of prescribed burns on species grouped by their frequency within the landscape before burning (common, less common, and rare) and their life‐form attributes (woody perennials, perennial herbs or geophytes, and annual herbs). Burn treatment influenced the response of rare species. In spring‐burn plots, the recruitment of rare annual herbs was promoted, differentiating this treatment from both autumn‐burn and unburnt plots. In autumn‐burn plots, richness of rare species increased across all life‐form groups, although composition remained statistically similar to control plots. Richness of rare woody perennials increased in control plots. For all other life‐form and frequency groups, the floristic composition of landscapes changed between survey years, but there was no effect of burn treatment, suggesting a likely effect of rainfall on species recruitment. A prescribed burn can increase the occurrence of rare species in a landscape, but burn characteristics can affect the promotion of different life‐form groups and thus affect functional diversity. Drought‐breaking rain likely had an overarching effect on floristic composition during our study, highlighting that weather can play a greater role in influencing recruitment and diversity in plant communities than a prescribed burn. Abstract : Prescribed burning can inadvertently affect plant rarity. We examined the influence of prescribed fire on plants in a temperate forest and found that prescribed burns can positively influence the presence of rare species. Burn characteristics, such as season and extent, can influence the type of life‐form promoted, for example, extensive spring burns favoring rare annual herbs. Managing disturbance to promote heterogeneous landscapes may help maintain rare species diversity on a landscape scale.